123 Detrimental effects of acute sleep deprivation on perceptual metacognition. (3rd May 2021) - Bigica, Marco; Jiang, Chunxiang; D'Onofrio, Ilenia; Liu, Zhishan; Song, Chen
Abstract: Introduction: Sleep deprivation (SD) impairs cognitive performance but its impact on metacognition – i.e. the ability to introspect about cognitive performance – is less clear. A few studies have assessed metacognitive accuracy after acute sleep deprivation in tasks of executive functions and found no impairments. However, whether SD has no influence on metacognition of other cognitive domains such as perception has not been investigated. In this study, we examined how metacognitive accuracy in perceptual decision tasks is affected by 32 hours of sustained wakefulness. Methods: 14 participants (3 males, aged 20-32) repeated four visual psychophysical tasks (orientation discrimination, two-flicker fusion, vernier acuity and a novel face/house discrimination in noise) at regular intervals during 32 hours of sustained wakefulness and once after 8 hours recovery sleep. In each task, we concurrently measured quantitative indices of perceptual threshold, confidence rating and metacognitive accuracy (i.e. how well confidence ratings discriminate correct vs incorrect perceptual judgements). Results: We observed a gradual increase of perceptual threshold in all tasks with increased time awake. Furthermore, metacognitive accuracy gradually decreased during sustained wakefulness in all tasks. Specifically, the decrease in metacognitive accuracy was driven by over-estimated confidence in trials when participants made incorrect perceptual judgements. After recovery sleep, perceptual thresholds were reset to baseline for all tasks, while metacognitive accuracy was reset to baseline for the orientation discrimination and two-flicker fusion tasks only. Conclusion: We showed that sustained wakefulness up to 32 hours increasingly impairs metacognitive accuracy in perceptual decision tasks. These results are consistent across different perceptual tasks, but are in contrast to previous studies showing preserved metacognition of executive functions after SD. Overall, this suggests that the fundamental mechanisms of perceptual metacognition may be similarly affected by sleep deprivation, but that SD selectively impacts different domains of metacognition, such as perceptual metacognition and metacognition of executive functions. Support (if any): MB - Cardiff University PhD Funding CS - Wellcome Trust 209192/Z/17/Z